Emotional intelligence program to develop the first social skills in sixth grade - Torres Estela, Juanita Miriam (2014)
The emotional intelligence program is oriented to improve the first social skills of students in primary education as an alternative solution to provide them with opportunities for success throughout his life. Currently, the Lourdes Maria educational institution of the Pomalca district there is little dedication in the area of tutoring by strengthens and developing personal and social skills that allow students to interact appropriately with their couples. The program that we present also aims to strengthen the tutorial work of teachers through methodological strategies contained in twelve sessions of learning, each of which develops an active sequence of exercises where predominate the modeling the skill by the teaching and practice of the students. There is a need to develop this type of programs in our schools to achieve emotionally intelligent students that establish good relationships and know how to interact in a positive manner with the others. Once, applied the emotional intelligence program we affirm that it was significant, since most of the students are located in the high category, it can be said that it was achieved that students know how to control their emotions and practicing properly their first social skills. With the positive results of our research we can demonstrate the effectiveness of the emotional intelligence program, giving of this manner to the teachers of country an alternative solution to develop the social skills of students.